Micromotions at the taper interface between stem and neck adapter of a bimodular hip prosthesis during activities of daily living. Issue 8 (1st April 2013) - Jauch, Sabrina Yvonne; Huber, Gerd; Sellenschloh, Kay; Haschke, Henning; Baxmann, Marc; Grupp, Thomas M.; Morlock, Michael M.
Abstract The stem–neck taper interface of bimodular hip endoprostheses bears the risk of micromotions that can result in ongoing corrosion due to removal of the passive layer and ultimately cause implant fracture. We investigated the extent of micromotions at the stem–neck interface and the seating behavior of necks of one design made from different alloys during daily activities. Modular hip prostheses (n = 36, Metha®, Aesculap AG, Germany) with neck adapters (CoCr29Mo6 or Ti6Al4V) were embedded in PMMA (ISO 7206‐4) and exposed to cyclic loading with peak loads ranging from walking (Fmax = 2.3 kN) to stumbling (Fmax = 5.3 kN). Translational and rotational micromotions at the taper interface and seating characteristics during assembly and loading were determined using four eddy‐current sensors. Seating during loading after implant assembly was dependent on load magnitude but not on material coupling. Micromotions in the stem–neck interface correlated positively with load levels (CoCr: 2.6–6.3 µm, Ti: 4.6–13.8 µm; p < 0.001) with Ti neck adapters exhibiting significantly larger micromotions than CoCr (p < 0.001). These findings explain why high body weights and activities related to higher loads could increase the risk of fretting‐induced implant failures in clinical application, especially for Ti–Ti combinations. Still, the role of taper seating is not clearly understood. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1165–1171, 2013